Sequential treatment failure in ESR1-mutant breast cancer: A case highlighting therapeutic resistance - Patel, Hardik; Shaikh, Imran; Bhattacharyya, Susrita (Indian Journal of Case Reports, 2026)
We report a case of a 37-year-old female with a known history of diabetes mellitus and hypothyroidism, diagnosed with hormone receptor-positive (HR+) infiltrating mucinous carcinoma of the right breast. The disease initially responded to endocrine therapy but later demonstrated resistance, with progression to widespread metastatic disease including lymph nodes, lungs, pleura, pericardium, bones, and brain. Subsequent molecular profiling revealed an estrogen receptor 1 (ESR1) mutation, prompting a change in treatment to elacestrant. Despite multiple lines of endocrine and targeted therapies (including cyclin-dependent kinase4/6 inhibitors and mammalian target of rapamycin inhibitors), the disease continued to progress, underscoring the aggressive nature of ESR1-mutant HR+ breast cancer and the challenges in its management.